2016
DOI: 10.1021/acsbiomaterials.6b00408
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-Mimetic Micelles for Dual Delivery of Antigens and Imidazoquinoline Adjuvants

Abstract: Vaccine design has undergone a shift towards the use of purified protein subunit vaccines, which offer increased safety and greater control over antigen specificity, but at the expense of immunogenicity. Here we report the development of a new polymer-based vaccine delivery platform engineered to enhance immunity through the co-delivery of protein antigens and the Toll-like receptor 7 (TLR7) agonist imiquimod (IMQ). Owing to the preferential solubility of IMQ in fatty acids, a series of block copolymer micelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 98 publications
0
25
0
Order By: Relevance
“… 19 , 20 Given their superior immunostimulatory potency, the NP/3pRNA complexes developed here also hold potential as vaccine delivery platforms, investigations that will be pursued in future work. Important to such efforts, the synthetic versatility of RAFT synthesis also allows for incorporation of reactive handles into carriers for covalent linkage of peptides and proteins, 20 , 46 offering a strategy to achieve codelivery of antigen and adjuvant, which has been widely demonstrated to enhance vaccine responses. 47 Similarly, by using reactive or functionalized chain transfer agents in polymer synthesis, these carriers are also highly amenable to incorporation of targeting ligands (e.g., antibodies, carbohydrates) to improve cell or organ specificity of RIG-I activation.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 19 , 20 Given their superior immunostimulatory potency, the NP/3pRNA complexes developed here also hold potential as vaccine delivery platforms, investigations that will be pursued in future work. Important to such efforts, the synthetic versatility of RAFT synthesis also allows for incorporation of reactive handles into carriers for covalent linkage of peptides and proteins, 20 , 46 offering a strategy to achieve codelivery of antigen and adjuvant, which has been widely demonstrated to enhance vaccine responses. 47 Similarly, by using reactive or functionalized chain transfer agents in polymer synthesis, these carriers are also highly amenable to incorporation of targeting ligands (e.g., antibodies, carbohydrates) to improve cell or organ specificity of RIG-I activation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These polymers have pH-responsive carboxylate pendant groups from MAA, and hydrophobicity from non-ionizable methacrylates, such as BMA, dodecyl methacrylate (DMA), lauryl methacrylate (LMA), and cholesteryl methacrylate (CMA). Previous studies found that incorporating a small portion of hydrophobic monomers (i.e., 1% DMA, 2% CMA or 10% LMA) in PMAA copolymers could enhance the interaction with lipid membranes significantly, compared with PMAA homopolymer (Cho et al, 2016;Sevimli et al, 2017;Wannasarit et al, 2019).…”
Section: Copolymers Of Maa or Aa With Hydrophobic Moietiesmentioning
confidence: 99%
“…These polymers have pH-responsive carboxylate pendant groups from MAA, and hydrophobicity from non-ionizable methacrylates, such as BMA, dodecyl methacrylate (DMA), lauryl methacrylate (LMA), and cholesteryl methacrylate (CMA). Previous studies found that incorporating a small portion of hydrophobic monomers (i.e., 1% DMA, 2% CMA or 10% LMA) in PMAA copolymers could enhance the interaction with lipid membranes significantly, compared with PMAA homopolymer (Cho et al, 2016 ; Sevimli et al, 2017 ; Wannasarit et al, 2019 ). However, a further increase of the hydrophobic moieties (i.e., 8% CMA and 40% LMA) in the copolymer led to decreased solubility and enhanced supermolecular assembly in aqueous solutions, which in turn decreased the interaction between polymer and lipid membranes (Sevimli et al, 2012 ; Wannasarit et al, 2019 ).…”
Section: Amphiphilic Carboxylate Polymers: History and Recent Developmentmentioning
confidence: 99%
“…Several approaches have emerged to co-assemble and co-deliver antigen and adjuvant using non-covalent interactions, including electrostatic or hydrophobic interactions, and other driving forces. For example, micelles and other particulate strategies have been used to deliver model antigens and either individual TLRas or defined combinations of TLRs [83] , [93] , [94] , [95] . Interestingly, one example of this approach demonstrates that co-incorporation of antigen and adjuvant enhances the potency of the response with minimal systemic inflammation [96] , an off-target side effect often associated with adjuvant delivery.…”
Section: Self-assembled Systems Can Create Design Guidelines For New mentioning
confidence: 99%